Phytofabrication of Selenium Nanoparticles From Emblica officinalis Fruit Extract and Exploring Its Biopotential Applications: Antioxidant, Antimicrobial, and Biocompatibility - Gunti, Lokanadhan; Dass, Regina Sharmila; Kalagatur, Naveen Kumar (Frontiers in Microbiology, 2019)
In the present study, phytofabricated selenium nanoparticles (PF-SeNPs) were prepared from aqueous fruit extract of Emblica officinalis in a facile, green, economic, tactic and eco-friendly way. The aqueous fruit extract of E. officinalis was found to be rich with various secondary metabolites including phenolics (59.18 ± 2.91 mg gallic acid equivalents/g), flavonoids (38.50 ± 2.84 mg catechin equivalents/g) and tannins (44.28 ± 3.09 mg tannic acid equivalents/g) and determined that highly appropriate for the biosynthesis of nanoparticles. The facile phytofabrication of PF-SeNPs was confirmed by UV-visible and FTIR spectroscopic analysis. The XRD pattern and Raman spectroscopy showed that synthesized PF-SeNPs were amorphous in nature. The Zeta potential analysis confirmed that PF-SeNPs were negatively charged (– 24.4 mV). The DLS analysis revealed that PF-SeNPs were in nano size and less aggregated with poly-dispersity index of less than 0.2. The SEM images depicted that PF-SeNPs were spherical in shape. The EDX analysis revealed that PF-SeNPs were constituted with Se (61.60%), C (29.96%) and O (4.41%). The HR-TEM analysis determined that PF-SeNPs were in nano size with an average diameter of 15 – 40 nm. The PF-SeNPs have offered fascinating bio-potential applications, such as antioxidant, antimicrobial and biocompatibility. They have also exhibited dose-dependent free radical scavenging activity, and EC50 was determined as 15.67 ± 1.41 and 18.84 ± 1.02 µg/mL for DPPH and ABTS assays, respectively. The PF-SeNPs has also shown the wide range of antimicrobial activity on foodborne pathogens, and it was found to be highly efficient on fungi followed by Gram-positive and Gram-negative bacteria. The biocompatibility of PF-SeNPs was assessed in N2a cells with much higher IC50 value (dose required to inhibit 50% of cell viability) compared to sodium selenite. Also, mitochondrial membrane potential (MMP) and caspase-3 were much less altered on treatment of PF-SeNPs related to sodium selenite. The cytotoxic studies clearly determined that PF-SeNPs was much less toxic and safer related to sodium selenite. Thus, PF-SeNPs could find suitable application as antioxidant and antimicrobial agent in food, biomedical, and pharmaceutical industry.